1996
DOI: 10.1093/toxsci/34.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid-Induced Epiphyseal Plate Closure in Guinea Pigs

Abstract: . (1996). Fundam. AppL Toxicol. 34,[91][92][93][94][95][96][97][98] Vitamin A and its derivatives (retinoids) have been known to cause premature epiphyseal closure in humans as an unwanted side effect of chronic treatment. The purpose of the present study was to determine if guinea pigs could serve as an animal model of retinoid-induced epiphyseal plate closure, and to utilize this model to study the mechanism. Weanling male Hartley guinea pigs were treated ip via osmotic pump for up to 14 days with vehicle or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
(15 reference statements)
1
15
0
2
Order By: Relevance
“…6A, second panel; Fig. 6B), as previously observed in response to other retinoid agonists, (36,37) but no other major obvious phenotype was noted. Palovarotene-treated mutants showed markedly reduced HO that was nearly absent in their forelimbs and much reduced in hindlimbs ( Fig.…”
Section: Palovarotene Reduces Spontaneous Ho and Improves Skeletal Masupporting
confidence: 82%
“…6A, second panel; Fig. 6B), as previously observed in response to other retinoid agonists, (36,37) but no other major obvious phenotype was noted. Palovarotene-treated mutants showed markedly reduced HO that was nearly absent in their forelimbs and much reduced in hindlimbs ( Fig.…”
Section: Palovarotene Reduces Spontaneous Ho and Improves Skeletal Masupporting
confidence: 82%
“…Current and proposed treatments for HO, including anti-inflammatory agents, pyrophosphate analogues, ionizing radiation therapy, BMP antagonists, and retinoic acid receptor agonists, all have the undesirable adverse effect of disrupting systemic bone homeostasis and inhibiting fracture repair. (70)(71)(72)(73)(74)(75) In stark contrast to these current or proposed therapies, we have previously reported that plasmin activity is essential for fracture repair and bone homeostasis. (30,39) Future studies are required to identify and investigate the complications and clinical feasibility of reducing a2AP to increase plasmin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as growth hormone, thyroid hormone, and glucocorticoids appear to affect skeletal maturation in humans (38). In addition, retinoid (41) and warfarin (42) toxicity can cause premature fusion. It is not clear whether these conditions cause ossification directly or indirectly by accelerating growth plate senescence.…”
Section: Fig 2 Effect Of Estrogen Treatment On Mean (ϯSem) Tibial Gmentioning
confidence: 99%